Rancang dan Bangun Mesin Filling Sari Kedelai dengan Pneumatik - Tresna Umar Syamsuri; Rahma Nur Amalia; Mudjiono (Politeknik Negeri Malang, 2022)
Currently, the industry is required to work quickly, optimally, and produce products in large and accurate quantities. Due to the high demand, home industries with simple technology are required to produce a lot of goods. One example of a household industry that has a lot of demand for its products is the soybean juice beverage industry. However, in the process of filling soy juice drinks into bottles, there are several shortcomings, including the process is still manual, spills easily, the amount of liquid is not appropriate or not constant, takes a long time, and drains a lot of energy. To maximize production results, a machine with a pneumatic system was made, where this system uses compressed air as the working medium and electricity as the control medium. The design of this filling machine is carried out using several methods such as observation, literature study, and making designs. Soybean filling machine is a tool produced in this study. The operation of the machine can be semi-automatic and automatic has a high level of accuracy and has an error of about 0.045%-0.09%. This filling machine can fill bottles with sizes ranging from 250 ml to 800 ml, besides that this machine is also equipped with a bottle counter that is already filled with drinks. The application of filling machines in home industries has the potential to increase the productivity of soybean juice drinks and the income of their owners.